Avaliação do ciclo de vida de agregado reciclado tratado com álcool polivinílico (PVA) na mitigação da pegada de carbono - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
The construction industry has been causing significant environmental impacts, and mitigating these impacts can involve the reuse of construction waste as a recycled aggregate, which also allows for a reduction in the carbon footprint due to the potential for CO2 sequestration in cementitious composites. To improve the absorption and density of recycled aggregates, several physical and chemical treatment techniques are available, including accelerated carbonation and polyvinyl alcohol (PVA). In addition to enhancing the technical properties of these aggregates, these treatments contribute to carbon sequestration via the formation of calcium carbonate. One way to assess the environmental contribution of treated recycled concrete aggregate (RCA) is through Life Cycle Assessment (LCA), which evaluates the environmental impacts of the processes and materials involved in its production. The objective of this study was to identify the sustainable contribution potential of recycled concrete aggregates treated with accelerated carbonation and PVA film through LCA to determine their carbon footprint. To this end, the production of the recycled aggregate in question was carried out, varying the compressive strength of the original concrete between 25MPa, 30MPa, 35MPa, and 40MPa, followed by the application of a 3% PVA film. To assess changes in the material’s characteristics and composition, physical-chemical and mineralogical characterization tests were performed. Based on these data, the calculation of CO2 equivalent emissions from the waste before and after accelerated carbonation with the PVA film was carried out, in conjunction with the determination of the carbon sequestration promoted by the treatment, to establish the reduction in the carbon footprint due to the application of the PVA film. The results showed that the carbonated compounds in the mortar adhered to the grains of the recycled aggregates, with the 25MPa aggregate standing out. After PVA treatment, there was a 60.36% increase in the presence of calcium carbonate due to the greater availability of pores for crystal formation and carbonatable compounds such as Ca(OH)2, C-S-H, C2S, C3S, and Mg(OH)2, which were present in smaller quantities in the other strength ranges. The other aggregates showed changes in absorption and specific gravity but exhibited less formation of carbonated compounds. Thus, compared to conventional carbonation processes, the use of PVA as a treatment for RCA was found to have potential for carbon sequestration, averaging 21.23kg of CO2 per m³ of RCA, making this methodology more competitive in the market.
Keywords: resíduo de construção e demolição; carbonatação; pva; sequestro de carbono; análise de ciclo de vida.; construction and demolition waste; carbonation; pva; carbon sequestration; life cycle analysis; Engenharia Sanitária e Ambiental